Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I would like to compute $$ \iint_{[0,1]^2} \frac{-x\ln(xy)}{1-xy} \mathrm dx \mathrm dy $$

Without going into detail, here is what I found:

$$ \int_{0}^{1}(\int_{0}^{1} \frac{-x\ln(xy)}{1-xy} \mathrm dx ) \mathrm dy=\int_{0}^{1}(-\sum_{n=0}^{\infty} \int_{0}^{1} x^{n+1}y^n\ln(xy) \mathrm dx)\mathrm dy $$

$$ \int_{0}^{1}\sum_{n=1}^{\infty}\frac{y^n}{(n+1)^2}\mathrm dy=\sum_{n=1}^{\infty} \frac{1}{(n+1)^3}\approx0.202 $$

However Wolfram gives: $$ \iint_{[0,1]^2} \frac{-x\ln(xy)}{1-xy} \mathrm dx \mathrm dy=1 $$

Where is the problem?

share|improve this question
    
W|A's answer is correct, as shown by the change of variables $(x,y)\to(x,z)$ with $z=xy$. –  Did Apr 9 '12 at 15:01
    
@Didier Could you show me how to do that? –  Pedro Tamaroff Apr 9 '12 at 23:48
    
@PeterT.off The OP does not seem interested... –  Did Apr 9 '12 at 23:51
    
@Didier That's why I phrased it as show me. Should I open a new question? –  Pedro Tamaroff Apr 9 '12 at 23:54
    
@PeterT.off: Whatever you do or do not do, answering here seems pointless. –  Did Apr 10 '12 at 6:30

1 Answer 1

up vote 5 down vote accepted

\begin{align*}\int_0^1x^{n+1}y^n\ln(xy)dx&=y^n\int_0^1x^{n+1}\ln xdx+y^n\ln y\int_0^1x^{n+1}dx\\ &=y^n\left[\frac{x^{n+2}}{n+2}\ln x\right]_0^1-y^n\int_0^1\frac{x^{n+2}}{n+2}\frac 1xdx +y^n\ln y\frac 1{n+2}\\ &=-\frac{y^n}{(n+2)^2}+y^n\frac{\ln y}{n+2}\\ &=\frac{y^n}{n+2}\left(\ln y-\frac 1{n+2}\right) \end{align*} and \begin{align*} \int_0^1\frac{-x\ln(xy)}{1-xy}&=-\sum_{n=0}^{+\infty}\int_0^1\int_0^1x^{n+1}y^n\ln(xy)dxdy\\ &=-\sum_{n=0}^{+\infty}\frac 1{n+2}\int_0^1y^n\left(-\frac{1}{n+2}+\ln y\right)dy\\ &=-\sum_{n=0}^{+\infty}\frac 1{(n+2)^2(n+1)}-\sum_{n=0}^{+\infty}\frac 1{n+2}\frac 1{n+1}\left(-\int_0^1y^{n+1}\frac 1ydy\right)\\ &=-\sum_{n=0}^{+\infty}\frac 1{(n+2)^2(n+1)}+\sum_{n=0}^{+\infty}\frac 1{(n+2)(n+1)^2}\\ &=-\sum_{n=0}^{+\infty}\frac 1{(n+2)(n+1)}\left(\frac 1{n+2}-\frac 1{n+1}\right)\\ &=\sum_{n=0}^{+\infty}\frac 1{(n+2)(n+1)}\\ &=\sum_{j=1}^{+\infty}\frac{j+1-j}{(j+1)j}\\ &=\sum_{j=1}^{+\infty}\frac 1j-\frac 1{j+1}=1 \end{align*} so Wolfram is right.

share|improve this answer
    
I'm realizing that I made mistake in my calculations... Thank you for your answer! –  Chon Apr 9 '12 at 18:32

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.